2021
DOI: 10.1111/bph.15518
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage extracellular traps aggravate iron overload‐related liver ischaemia/reperfusion injury

Abstract: Background and Purpose: Macrophages regulate iron homeostasis in the liver and play important role in hepatic ischaemia/reperfusion (I/R) injury. This study investigates the role of macrophages in iron overload-related hepatocyte damage during liver I/R. Experimental Approach: Liver biopsies from patients undergoing partial hepatectomy with or without hepatic portal occlusion were recruited and markers of hepatocyte cell death and macrophage extracellular traps (METs) were detected.A murine hepatic I/R model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…On day 21 and 42, the contents of alkaline phosphatase (ALP), alanine aminotransferase (ALT), aspartate aminotransferase (AST), albumin (ALB), total protein (TP), creatinine (CREA), urea nitrogen (UN), glucose (GLU), total antioxidant capacity (T-AOC), catalase (CAT), and malondialdehyde (MDA) in serum were measured by the corresponding commercial kits purchased from Nanjing Jiancheng Bioengineering institute (Nanjing, China), according to the manufacturer's instructions. Serum Fe contents were detected according to the method reported by Wu et al [24]. The serum biochemical parameters with the corresponding commercial kit number are listed in Table 2.…”
Section: Analysis Of Serum Biochemical Parametersmentioning
confidence: 99%
“…On day 21 and 42, the contents of alkaline phosphatase (ALP), alanine aminotransferase (ALT), aspartate aminotransferase (AST), albumin (ALB), total protein (TP), creatinine (CREA), urea nitrogen (UN), glucose (GLU), total antioxidant capacity (T-AOC), catalase (CAT), and malondialdehyde (MDA) in serum were measured by the corresponding commercial kits purchased from Nanjing Jiancheng Bioengineering institute (Nanjing, China), according to the manufacturer's instructions. Serum Fe contents were detected according to the method reported by Wu et al [24]. The serum biochemical parameters with the corresponding commercial kit number are listed in Table 2.…”
Section: Analysis Of Serum Biochemical Parametersmentioning
confidence: 99%
“…A growing body of evidence suggests that ferroptosis may serve as a promising target for the prevention and treatment of ASH. Ferroptosis, an iron-dependent form of nonapoptotic cell death (Li et al, 2020), occurs through an increase in cellular phospholipid peroxidation in the context of a compromised phospholipid peroxide repair system (Wang et al, 2021;Wu et al, 2021b). With respect to ASH, liver cells are more susceptible to ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it was found that macrophage extracellular trap was increased in co-cultured experiment subjected to IRI. Moreover, macrophage extracellular trap aggravated ferroptosis, thereby causing an increasing post-ischemia liver damage [ 71 ].…”
Section: Hepatic Microenvironmentmentioning
confidence: 99%